2010
DOI: 10.1177/1527002510363100
|View full text |Cite
|
Sign up to set email alerts
|

Top Clubs’ Performance and the Competitive Situation in European Domestic Football Competitions

Abstract: The increase in payouts to European football clubs appearing in the Union of European Football Associations (UEFA) Champions League (CL) in 1999-2000 had a lasting impact on the performance of top clubs in domestic football leagues. This policy change is treated as a natural experiment to compare the level of competitive balance in five top European leagues (England, Spain, Italy, Germany, and France) before and after the turn of the millennium. Based on several competitive balance measures, this article revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 20 publications
6
106
0
2
Order By: Relevance
“…Moreover, our results show that this relationship can be transferred to success in UEFA competitions. This result has been expected given the growing importance of UEFA competitions for Europe's elite football clubs [10,12]. Std.…”
Section: Panel Regressionmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, our results show that this relationship can be transferred to success in UEFA competitions. This result has been expected given the growing importance of UEFA competitions for Europe's elite football clubs [10,12]. Std.…”
Section: Panel Regressionmentioning
confidence: 83%
“…Szymanski [12] (p. 204) puts it into a nutshell by stating that " [t]here is no doubt that the big clubs view success in the Champions League as their primary objective." Particularly, the change in the payout system of the UEFA Champions League has shifted incentives from national to international competitions and generated a small group of elite clubs in Europe [10,12]. Teams participating in UEFA competitions are able to generate direct revenues through success and participation bonuses from UEFA.…”
Section: Financial Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this background, the increasing imbalance of the top 5 national football leagues in Europe as well as of the UEFA Champions League may reflect a worrying development (Pawlowski, Breuer & Hovemann, 2010). Moreover, other European football leagues also increasingly become less balanced (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, season-aggregate attendance has actually increased in some leagues (e.g. Germany and England), even as European leagues have become increasingly dominated by a small number of teams over the last decade (Flores, Forrest & Tena 2010;Pawlowski, Breuer & Hovemann 2010;Pawlowski 2013b: 2). This motivated further research into a completely new direction, which Zimbalist (2002: 112) already suggested in 2002 by stating, that "the best measure of competitive balance is the one to which fans show the greatest sensitivity".…”
Section: Introductionmentioning
confidence: 99%